An Assessment on Green Campus Rating of the University of Lampung Main Campus - Kustiani, Ika; Matemba, Esther Elly; Widyawati, Ratna; Putra, Rahmad Syah (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2024)
Currently, people perceive higher education as an industry that operates within a specific area. Therefore, the concept of a green campus or eco-campus can be linked to the concept of a green neighborhood. The aim of carrying out this assessment is to determine the performance of the Gedong Meneng Campus of the University of Lampung based on the Greenship Neighborhood Rating Tool criteria from the Green Building Council Indonesia (GBCI). The research data was obtained primarily based on observations, along with secondary data in the form of formal documents such as the campus master plan and several other documents. Based on the assessment result, despite the fact that the campus has implemented principles of the sustainable green neighborhood concept, it has not been able to obtain even the lowest rank of Greenship Neighborhood. With a score of 38 out of a total of 117 points, or 34.48%, it is only a small difference to achieve a bronze rank. The assessment results led to the formulation of a set of cost-free management solutions aimed at transforming the campus area into a green campus neighborhood. By improving community welfare, movement, and connectivity, as well as land ecology criteria, it is expected that the score would increase by 22 points, resulting in a Silver Rank that can be achieved.